Foxp3+ regulatory T cells are activated in spite of B7‐CD28 and CD40‐CD40L blockade. Issue 4 (22nd February 2013) - Vogel, Isabel; Verbinnen, Bert; Maes, Wim; Boon, Louis; Van Gool, Stefaan W.; Ceuppens, Jan L.
<x xml:space="preserve">Abstract</x> Costimulatory signals are required for priming and activation of naive T cells, while it is less clear how they contribute to induction of regulatory T (Treg)‐cell activity. We previously reported that the blockade of the B7‐CD28 and CD40L‐CD40 interaction efficiently suppresses allogeneic T‐cell activation in vivo. This was characterized by an initial rise in Foxp3+ cells, followed by depletion of host‐reactive T cells. To further investigate effects of costimulatory blockade on Treg cells, we used an in vitro model of allogeneic CD4+ cell activation. When CTLA‐4Ig and anti‐CD40L mAb (MR1) were added to the cultures, T‐cell proliferation and IL‐2 production were strongly reduced. However, Foxp3+ cells proliferated and acquired suppressive activity. They suppressed activation of syngeneic CD4+ cells much more efficiently than did freshly isolated Treg cells. CD4+ cells activated by allogeneic cells in the presence of MR1 and CTLA‐4Ig were hyporesponsive on restimulation, but their response was restored to that of naive CD4+ cells when Foxp3+ Treg cells were removed. We conclude that natural Treg cells are less dependent on B7‐CD28 or CD40‐CD40L costimulation compared with Foxp3− T cells. Reduced costimulation therefore alters the balance between Teff and Treg‐cell activation in favor of Treg‐cell activity.